IMPLEMENTASI METODE LEE & OWENS PADA MULTIMEDIA PEMBELAJARAN INTERAKTIF - Ramadhani, Denisa Sri; Swara, Ganda Yoga; Minarni, Minarni; Anisya, Anisya; Warman, Indra (Ensiklopedia of Journal, 2025)
This study aims to design and develop an interactive learning media titled “Learning About the Introduction to the Solar System”, based on Android. The background of this research is that the learning process at the school still relies on conventional methods such as books, planetarium teaching aids, and blackboards, which are less effective in improving students' understanding. To address this issue, this study designs interactive learning multimedia to assist teachers in delivering lessons and to help enhance sixth-grade students’ understanding of the solar system material. The 3D interactive solar system learning media has been successfully designed using Unity 3D and Blender software. The result of this design process is an application in .apk format that can be installed on Android-based smartphones. This interactive multimedia is equipped with various features such as material introduction, evaluations/quizzes, and educational puzzle games that can be accessed directly by students through Android devices. With the presence of this learning media, it is expected that students will more easily understand solar system concepts visually and interactively, and that it will also assist teachers in delivering the material in a more engaging and effective way.Keywords: Interactive Multimedia, Solar System, Unity 3D, Android, Learning Media